Keragaman Lumut Kerak (Lichenes) di Resort 6 Taman Nasional Batang Gadis (TNBG) Sumatera Utara - Eka Nuryani; Melfa Aisyah Hutasuhut; Zahratul Idami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the types of lichens, thallus types, and diversity index of lichens found in Resort 6 of Batang Gadis National Park. The method used in this study is an exploratory survey method with a squared plot technique using purposive sampling. The results of the study, there are 25 types of lichens from 13 families. The most commonly found family is the Parmeliaceae family and the most commonly found species is Lepraria sp. There are three types of thallus found in lichens, namely crustose, foliose, and fruticose types. There are 14 types of crustose-shaped lichens, 10 types of foliose shaped like leaves, and 1 type of fruticose shaped like dangling ribbons. The lichenes diversity index value is 2.96. From the results of the study it can be concluded that the diversity of lichens shows moderate diversity with a moderate distribution of individuals of each type. This also shows that the Batang Girls Resort 6 National Park area still has good air quality. Keywords: Diversity, Lichens (lichenes), Batang Gadis National Park